Sedation/Anestehesia Experiences During Magnetic Resonance Imaging Procedure in the Pediatric Patients - Bedih Balkan; Mesut Türk; Döndü Genç Moralar; Selda Yaşaroğlu; Abdulkadir Yektaş; Gülsüm Oya Hergünsel (Galenos Yayinevi, 2018)
Introduction: Sedation is often needed for magnetic resonance imaging (MRI) in pediatric patients for diagnostic purposes. In this study, we aimed to present anesthesia techniques and complications that occurred during sedation in pediatric patients. Methods: A total of 337 pediatric patients, in whom MRI was performed with sedation between January 1, 2016 and December 31, 2016, were retrospectively reviewed. The procedure, anesthetic drugs used, complications, and the need for additional medications were recorded. The patients were divided into 3 groups. Group 1: MRI procedure lasted 15 minutes, group 2: MRI procedure lasted 15-30 minutes and group 3: MRI procedure lasted more than 30 minutes. Within the groups, subgroup evaluations were made according to the type of anesthetic drug used. Results: There was no statistically significant effect of drug types used on complication development (bradicardia, hypoxia) and additional drug requirements in binary comparisons among subgroups (p=0.655, p=0.655 and p=0.317). In comparison of the groups according to the duration of the MRI procedure, complication development and need for additional medication were found to increase with prolonged imaging time (p=0.008, p=0.012 and p=0.02). Conclusion: Combinations of anesthetic and sedative drugs used during MRI in the pediatric patient group have no effect on complication development (bradicardia, hypoxia) and additional drug need. However, as the duration of the imaging procedure increases, complications and need for additional medication increase.